Biological features and potential of yield of energy cultures of the family of thin-skinned in the conditions of Ukraine - Курило, В. Л.; Рахметов, Д. Б.; Кулик, М. І. (Scientific Progress & Innovations, 2018)
The article substantiates the necessity of comprehensive study and cultivation of energy crops on marginal lands in the conditions of Ukraine for obtaining biofuel. Biological and morphological characteristics and illustrative material of energy cultures from the family of fine-toned ones are presented. Understanding the morphological and biological features and the ratio of energy crops to environmental conditions will allow them to be placed rationally in certain soil and climatic zones of Ukraine, and to select the optimal elements of growing technology. This will ensure conditions close to those favorable for the growth and development of plants, and will allow obtaining a large, energy-intensive phytomass. The harvest of the phytocoagulants of energy crops is expedient for use in the production of biofuel and energy production.